Construction of wells on the territory of non-native steppes of the Stavropol province in the late 19th–early 20th centuries: historical analysis and socio-economic significance - B. V. Ochirov (Nomadic Civilization: Historical Research, 2025)
This study, based on archival data, examines the situation with water supply in the territory of the nomadic peoples of the Stavropol province in the late 19th — early 20th centuries. During the period under study, water supply was mainly associated with the construction of wells, including artesian wells. The article describes in detail the possibilities and conditions for the creation of such wells, as well as the specific circumstances and difficulties that the steppe dwellers encountered during their construction. A study of water supply in the nomadic steppes of the Stavropol province shows that the creation of artesian wells was a difficult, complex and expensive process. To successfully complete such complex tasks, not only knowledge and experience were required, but also a certain determination on the part of the authorities and society. Public judgments of nomadic societies emphasized the importance and urgency of solving the water supply in foreign territories. The local administration helped in every way in finding specialized firms and specialists who could, if possible, accurately find water veins in the steppes, quickly and efficiently drill artesian wells. Thanks to the work carried out, not only did the water supply of the population improve, but problems with watering for livestock were also solved. The presence of man-made water resources in the form of artesian wells and natural reservoirs also contributed to the development of gardens and forests. The use of artesian wells contributed to the implementation of measures aimed at preventing desertification in the steppe regions where tribes roamed. In addition, high-quality water supply stimulated the transition of nomads to a sedentary lifestyle. In general, the development of water resources of the steppes of the Stavropol province, of course, was of great importance for the region as a whole and the steppe arid regions in particular in terms of socio-economic development, in economic and everyday life.